2010
DOI: 10.1103/physreve.81.061301
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure evolution in density relaxation by tapping

Abstract: The density relaxation phenomenon is modeled using both Monte Carlo and discrete element simulations to investigate the effects of regular taps applied to a vessel having a planar floor filled with monodisperse spheres. Results suggest the existence of a critical tap intensity which produces a maximum bulk solids fraction. We find that the mechanism responsible for the relaxation phenomenon is an evolving ordered packing structure propagating upwards from the plane floor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
19
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 51 publications
8
19
0
Order By: Relevance
“…In recent years, the dependency of the steady state packing fraction, φ, on the tapping intensity, Γ, has been shown to be nonmonotonic; presenting a minimum at relatively high values of Γ for disks and spheres [2,3], and a maximum at very low Γ for spheres [4]. In general, the symbol Γ is used for the reduced peak acceleration given to the system during a tap.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the dependency of the steady state packing fraction, φ, on the tapping intensity, Γ, has been shown to be nonmonotonic; presenting a minimum at relatively high values of Γ for disks and spheres [2,3], and a maximum at very low Γ for spheres [4]. In general, the symbol Γ is used for the reduced peak acceleration given to the system during a tap.…”
Section: Introductionmentioning
confidence: 99%
“…over-compression or tapping/driving (data not shown). Both (isotropic) modes of deformation lead to more compact, better packed configurations [21,167,220]. Considering different system sizes, and different preparation procedures, we confirmed that the jamming regime is the same (within fluctuations) for all the cases considered, see Appendix Fig.…”
Section: Cyclic Isotropic Over-compressionsupporting
confidence: 61%
“…Over-compressing a soft granular assembly is analogous to tapping [167,220] more rigid ones, in so far that both methods lead to more compact packing structures, i.e., both represent isotropic perturbations. These changes are shown in Fig.…”
Section: Slow Dynamics Modelmentioning
confidence: 99%
“…This also appears to be the case for higher space dimensions, and we intend to address this in a forthcoming paper, where we shall present a detailed investigation of solitons and other wave-like phenomena. These results will be compared with the experimental findings on various granular flow regimes such as the types in Rosato et al [22,23] in accordance with our continuing project on the development of dynamical systems based methods for predicting particulate dynamics (cf. [6]).…”
Section: Epiloguementioning
confidence: 95%
“…[6,17,23,[23][24][25]). It took the form of the following integro-partial differential equation (IPDE):…”
Section: Bsr Field Equationsmentioning
confidence: 99%